The Mediatization of “SARA” Conflict in Indonesian Online Media - Eni Maryani; Detta Rahmawan; Irma Garnesia (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
This study aims to analyses the news on "Aksi Damai" or "Peaceful Protest" occurred on December 2, 2016, in Jakarta related to the incumbent Jakarta Governor, Basuki Tjahaja Purnama or Ahok, over a blasphemy case. The "212 Peaceful Protest" is a protest conducted by several hardliner Muslim groups against Ahok, a Chinese Christian. Ahok was accused of a blasphemy-related to his statements about politicians who exploit a verse from the Holy Qur'an, to win the elections. The study uses a concept of mediatizations with quantitative and qualitative methods to collect data through content analysis, observation, and interviews. The research subject is two online media in Indonesia, Republika.co.id and Metrotvnews.com. The news from Republika.co.id and Metrotvnews.com are being collected from November 28 to December 4, 2016. In Indonesia, Republika.co.id is considered as a media that is oriented toward Muslim agenda, while Metrotvnews.com is oriented toward nationalism agenda. The results show that both Republika.co.id and Metrotvnews.com build a media logic or mediatizations related to Ahok's blasphemy cases. Republika.co.id emphasizes a narrative on divinity and piety logic, while Metrotvnews.com builds a narrative on the importance of national unity and legal political logic. The substance this study can be concluded that efforts to disseminate the values of tolerance and appreciate the noble values of humanity in a multicultural society must be carried on.